Online and offline physical education quality assessment based on mobile edge computing - Xu Ji (Nonlinear Engineering, 2024)
Every institution in China has undergone reform and piloting based on its unique situation to enhance the quality of instruction as a result of the ongoing advancement of the times and the educational idea in the information age. The effectiveness of education is increased by hybrid teaching, which combines offline and online approaches. It empowered educators and motivates learners to take responsibility for their learning. Classes in physical education (PE) that place a strong emphasis on training and technical performance are especially well-suited for hybrid instruction. This mode improves teaching abilities and supports the long-term growth of education. As a result, we offer an online and offline technique for assessing the quality of PE instruction that is relied on mobile edge computing (MEC). With the use of the target, index, weight, and standard assessments, this study builds a quality evaluation index (QEI) approach for PE that combines online and offline techniques. Assessing the corresponding significance of every index, factor, and cluster analysis compresses index elements. The weights of the QEIs for integrated instruction are determined using MEC. The efficacy of combined PE is assessed using the fuzzy logic-based comprehensive assessment methodology. According to the analytical model, this strategy increases teaching quality while reducing costs and mistakes and improves assessment effectiveness. The experimental results proved that the proposed model has provided an accuracy of 95.98%.